0688 Insomnia Symptom Severity Predicts Greater Alcohol Use During the COVID-19 Pandemic: A Longitudinal Study. (25th May 2022) - Bell, Jessica; Egeler, Mara; Snyder, Hope; Walker, Jamie; Hire, Veronica; Vargas, Ivan
Abstract: Introduction: Individual stress levels undeniably increased following the start of the COVID-19 pandemic. Not surprisingly, sleep problems, including insomnia, have intensified during the pandemic due to the increase in overall stress levels. The impact that greater insomnia has had on other health outcomes, for example problematic drinking, has yet to be examined. Therefore, the aim of the present study was to assess whether greater insomnia symptom severity predicted future alcohol use patterns (i.e., frequency and severity). Methods: The study used data from a nationwide sample of 2, 979 who were surveyed at two different points during the COVID-19 pandemic (T1 = initial months after the start of the pandemic [April – June 2020]; T2 = 10-12 months later). Of those, 1, 971 adults (mean age = 46.0 years; 80% women) reported having had an alcoholic beverage during the past 3 months and were included in the subsequent analyses. Insomnia symptom severity was assessed at both time points using the Insomnia Severity Index (ISI). Self-reported alcohol frequency (i.e., days per week) and severity (i.e., drinks per day) were assessed at T2. Results: At T2, participants reported drinking alcoholic beverages (mean ± standard deviation) 2.7 ± 2.1 days during a typical week and drinking 1.8 ± 1.1 alcoholic beverages on days they did drink. According to results from separate multiple regression analyses, where T1 ISI scores were entered as the independent variable and alcohol frequency and severity were entered as the dependent variables, total ISI scores at T1 were associated with less frequent (β = -0.075, p = .001) but more severe drinking patterns (β = .088, p < .001). These associations remained significant while controlling for current insomnia symptom severity. Conclusion: Baseline insomnia symptom severity was a predictor of future alcohol use patterns. Specifically, people with greater insomnia at T1 reported, on average, less frequent drinking (i.e., fewer days per week), yet greater consumption on days that they did drink alcohol. These data highlight the importance of assessing the impact that insomnia has had (and continues to have) on other behavioral health outcomes during the ongoing pandemic. Support (If Any): K23HL141581 (PI: Vargas); R25HL10544 (PI: Jean-Louis); K24AG055602 (PI: Perlis)